2018
DOI: 10.1186/s12958-018-0438-7
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and basal androstenedione are independent risk factors for miscarriage in polycystic ovary syndrome

Abstract: BackgroundThere is limited literature investigating the effects of body mass index (BMI) and androgen level on in vitro fertilization (IVF) outcomes with a gonadotropin-releasing hormone (GnRH)-antagonist protocol in polycystic ovary syndrome (PCOS). Androgen-related variation in the effect of body mass index (BMI) on IVF outcomes remains unknown.MethodsIn this retrospective study, 583 infertile women with PCOS who underwent IVF using the conventional GnRH-antagonist protocol were included. Patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 21 publications
1
44
1
1
Order By: Relevance
“…Outcomes of interest were reported in 11182 patients in 17 retrospective cohort studies ( 20 26 , 28 , 30 – 36 , 40 , 41 ), three prospective cohort studies ( 38 , 39 , 42 ) and two case-control studies ( 27 , 37 ). Fourteen studies were conducted in China ( 22 , 23 , 25 , 28 , 30 – 33 , 35 , 36 , 38 , 39 , 41 , 42 ), five in the USA ( 20 , 21 , 24 , 26 , 27 ), and the remaining three in Japan ( 37 ), Turkey ( 34 ), and Australia ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Outcomes of interest were reported in 11182 patients in 17 retrospective cohort studies ( 20 26 , 28 , 30 – 36 , 40 , 41 ), three prospective cohort studies ( 38 , 39 , 42 ) and two case-control studies ( 27 , 37 ). Fourteen studies were conducted in China ( 22 , 23 , 25 , 28 , 30 – 33 , 35 , 36 , 38 , 39 , 41 , 42 ), five in the USA ( 20 , 21 , 24 , 26 , 27 ), and the remaining three in Japan ( 37 ), Turkey ( 34 ), and Australia ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes of interest were reported in 11182 patients in 17 retrospective cohort studies ( 20 26 , 28 , 30 – 36 , 40 , 41 ), three prospective cohort studies ( 38 , 39 , 42 ) and two case-control studies ( 27 , 37 ). Fourteen studies were conducted in China ( 22 , 23 , 25 , 28 , 30 – 33 , 35 , 36 , 38 , 39 , 41 , 42 ), five in the USA ( 20 , 21 , 24 , 26 , 27 ), and the remaining three in Japan ( 37 ), Turkey ( 34 ), and Australia ( 40 ). Seventeen studies measured BMI ( 20 26 , 30 – 32 , 34 38 , 41 , 42 ), four assessed age ( 28 , 30 , 37 , 40 ), three evaluated insulin resistance ( 30 , 37 , 42 ), five investigated chromosome aberrations ( 26 , 30 , 31 , 33 , 39 ), and the other four assessed hyperandrogenism ( 27 , 30 , 37 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that the long‐term deleterious effect of estrogen alone for women with PCOS could be related to endometrial impairment 8 10 . A hyper‐androgenic environment and overproduction of luteinising hormone (LH) as well as inflammatory factors related to endocrine disorders were also reported to affect endometrial receptivity in women with PCOS 11,12 .…”
Section: Introductionmentioning
confidence: 99%